Effects of Stress During Pregnancy on Maternal and Fetal Health: A Systematic Review - Hasriantirisna, Hasriantirisna; Nanda, Kiki Riskianti; Munawwarah. M, St. (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study aims to systematically review the effects of stress during pregnancy on maternal and fetal health, with a focus on the physiological, psychological, and socioeconomic dimensions. Research Design and Methodology: A systematic review design was adopted, analyzing peer-reviewed articles published between 2000 and 2023. The review included studies focusing on human subjects that examined various stress-related factors and their impact on pregnancy outcomes. Data was collected through exhaustive searches of electronic databases, followed by thematic analysis and meta-analysis where appropriate. Findings and Discussion: The review reveals significant impacts of prenatal stress on maternal and fetal health. Elevated maternal cortisol levels are linked to adverse birth outcomes, such as preterm birth and low birth weight. Prenatal stress also causes structural changes in fetal brain development, leading to long-term cognitive and behavioral issues. Systemic inflammation resulting from chronic stress exacerbates these effects. Socio-economic and cultural disparities further intensify the negative impacts of prenatal stress. Tailored interventions, including culturally competent care and improved access to healthcare, are essential for mitigating these effects. Implications: The study underscores the need for comprehensive stress management programs for pregnant women, policies enhancing healthcare accessibility, and interventions addressing socio-economic stressors. Future research should focus on longitudinal studies and exploring genetic mechanisms to develop more effective interventions. These efforts are crucial for improving maternal and fetal health outcomes globally.